An Integrated Literature Review of Time-on-Task Effects With a Pragmatic Framework for Understanding and Improving Decision-Making in Multidisciplinary Oncology Team Meetings - Soukup, Tayana; Lamb, Benjamin W.; Weigl, Matthias; Green, James S. A.; Sevdalis, Nick (Frontiers in Psychology, 2019)
Multidisciplinary oncology team meetings (MDMs) or tumor boards, like other MDMs in healthcare, facilitate the incorporation of diverse clinical expertise into treatment planning for patients. Decision-making (DM) in MDMs is carried out repeatedly until all patients put forward for discussion have been reviewed. Despite continuing financial pressure and staff shortages, the workload of cancer MDMs, and therefore meeting duration continue to increase (up to 5-hours) with patients often receiving less than 2-minute of team input. This begs the question as to whether the current set-up is conducive to achieve optimal DM, which multi-specialty teams were set out to achieve in the first place. Much of what it is known however about the effects of prolonged cognitive activity comes from various subfields of science, leaving a gap in applied knowledge relating to complex healthcare environments. The objective of this review was thus to synthesize theory, evidence and clinical practice in order to bring the current understanding of prolonged, repeated DM into the context of cancer MDMs. We explore how and why prolonged cognitive activity affects task performance in such settings, and what strategies can be employed by cancer teams to counteract negative effects and improve quality and patient safety. In the process, we propose a new (unified) theory and we highlight promising research avenues for closing the research-to-practice gap. Theoretical and empirical evidence reviewed in this paper suggests that over prolonged time spent on a task, repeated DM is cognitively taxing, leading to fatigue and performance decrements. This deterioration is associated with various cognitive-behavioral pitfalls, including decreased attentional capacity and reduced ability to effectively evaluate choices, as well as less analytical DM and increased reliance on heuristics. In order to ensure safety and consistently high quality of care for all patients, future research and interventions in cancer MDMs should address decision fatigue with evidence-based cognitive strategies proposed in this review that range from food intake and short breaks to rewards and mental exercises. The fatigue that arises in healthcare workers as a result of the intensity (time-on-task) and complexity of the workload require more research, regulatory focus and recognition.